2014
DOI: 10.7603/s40680-015-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

Solunum fizyoterapisinde özelleşme: hermes projesi

Abstract: Sayın Editör, Fizyoterapide özelleşme, belirli bir fizyoterapi alanında, en üst düzey uzmanlaşma ile gerçekleşir. Dünya Fizyoterapi Konfederasyonu lisansüstü özel-leşme eğitimini sekiz alanda tanımaktadır (1). Bu alanlardan biri "kardiyovasküler ve pulmoner rehabilitasyon" kapsamında yer alan "solunum fizyoterapisi"dir. Avrupa Solunum Derneği (ERS)'nin Fizyoterapi alt grubu önderliğinde, üyesi bulunduğum "ERS Solunum Fizyoterapisi Çalışma Grubu" tarafından gerçekleştirilen "HERMES Solunum Fizyoterapisi Projesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Naeemah et al have reported that not only testosterone level was elevated in PCOS women, but also luteinizing hormone was elevated as well [23]. PCOS women have shown elevated status of oxidative stress in the circulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Naeemah et al have reported that not only testosterone level was elevated in PCOS women, but also luteinizing hormone was elevated as well [23]. PCOS women have shown elevated status of oxidative stress in the circulation.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we have found similar results, in which TOS level was increased but GSH level was reduced. Furthermore, Naeemah et al have reported a significant increase in the level of TOS in PCOS women, and attributed this systemic oxidative stress to the onset of insulin resistance [23]. Kanafchian et al have reported a significant reduction in the total antioxidant capacity of PCOS women, which suggested a systemic oxidative stress [25].…”
Section: Discussionmentioning
confidence: 99%